Parallel Graph Transformation based on Merged Approach - Aouat, Asmaa; Deba, El Abbassia (IAES International Journal of Robotics and Automation (IJRA), 2013)
Graph transformation is one of the key concepts in graph grammar. In order to accelerate the graph transformation, the concept of parallel graph transformation has been proposed by different tools such as AGG tool. The theory of parallel graph transformation used by AGG just allows clarifying the concepts of conflict and dependency between the transformation rules. This work proposes an approach of parallel graph transformations which enables dependent transformation rules to be executed in parallel.